THE IMPACT OF PUBLIC DEBT ON THE TWIN IMBALANCES IN EUROPE: A THRESHOLD MODEL - Šuliková, Veronika; Tykhonenko, Anna (Economic Annals, 2017)
Recent empirical research rejecting twin deficits in indebted countries and current account imbalances adjustment in Europe led to the idea to test the twin imbalances at different public debt-to-GDP intervals. The analysis covers 14 EU countries over the time period 1995-2012. A panel data threshold model with fixed effects estimates two debt-toGDP thresholds (40.2% and 96.6%), which determine three debt-to-GDP intervals in the twin relationship. If public debtto-GDP is less than 40.2%, the model determines a negative relationship (twin divergence) between budget balance and current account. Twin deficits (surpluses) are confirmed exclusively if debt-to-GDP is in the interval between 40.2% and 96.6%. A twin divergence is also confirmed if public debt-to-GDP is more than 96.6% (e.g., as in Greece and Italy). The results confirm that increased indebtedness in European countries contributed to their current account imbalance adjustment.